2009
DOI: 10.3923/pjbs.2009.173.177
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Lead Sub-Chronic Toxicity on Recognition Memory and Motor Activity of Wistar Rat

Abstract: The aim of this research was to investigate the impact of lead nitrate administered in drinking water during 90 days (sub-chronic toxicity), on body weight gain, motor activity, brain lead accumulation and especially on recognition memory of Wistar rats. Two groups of young female Wistar rats were used. Treated rats received 20 mg L(-1) of lead nitrate diluted in drinking water, while control rats received drinking water only, for 3 months. An evolution of body weight, motor activity, object recognition memory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 5 publications
2
11
0
Order By: Relevance
“…Introduction) reported deficits in object recognition (Azzaoui et al, 2009) and in spatial memory (Kasten-Jolly et al, 2012), similar to those found in the current study. Object recognition and spatial memory are sub-served by brain regions that overlap olfactory recognition memory pathways including the prefrontal, entorhinal and perirhinal cortices, and the hippocampus/dentate gyrus (Jesseberger et al, 2009; Parron et al, 2006; Rinaldi et al, 2007; Winters and Bussey, 2005).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Introduction) reported deficits in object recognition (Azzaoui et al, 2009) and in spatial memory (Kasten-Jolly et al, 2012), similar to those found in the current study. Object recognition and spatial memory are sub-served by brain regions that overlap olfactory recognition memory pathways including the prefrontal, entorhinal and perirhinal cortices, and the hippocampus/dentate gyrus (Jesseberger et al, 2009; Parron et al, 2006; Rinaldi et al, 2007; Winters and Bussey, 2005).…”
Section: Discussionsupporting
confidence: 90%
“…For example, in adulthood, BALB/c mice chronically exposed to 20 ppm lead acetate delivered in dam’s drinking water had diminished memory (object recognition memory task) as compared to controls (Azzaoui et al, 2009). In a similar study, as compared to controls, adult Wistar rats chronically exposed to 20 ppm of lead in dam’s drinking water had diminished spatial memory (water maze) (Kasten-Jolly et al, 2012) (blood lead levels were not reported).…”
Section: Introductionmentioning
confidence: 99%
“…In a study of adult Wistar rats with and without exposure to 20 ppm lead acetate delivered in dams’ drinking water during development, low-level lead-exposed animals had decreased recognition memory (novel object recognition task), and increased exploratory ambulation (open field task) (Azzaoui, Ahami, and Khadmaoui, 2009). In another study of adult Sprague–Dawley rats exposed to 5 and 50 ppm lead acetate delivered in dams’ drinking water, the lowest exposure group had decreased exploratory ambulation on an open field task (Reiter, Anderson, Laskey, and Cahill, 1975) (specific BLL values not reported).…”
Section: Introductionmentioning
confidence: 99%
“…In mouse and rodent models, early chronic exposure to Pb resulted in decreased memory, and abnormal motor and exploratory behavior (Azzaoui et al, 2009; Kasten-Jolly et al, 2012; Leasure et al, 2008). The mechanisms by which early chronic exposure to Pb alters brain structure and function have not been identified.…”
Section: Introductionmentioning
confidence: 99%